Loss rate of net primary productivity under drought stress on the Yinshanbeilu of Inner Mongolia, China - Sinan, Wang; Wu, Yingjie; Wang, Wenjun; Guo, Jianyin; Li, Mingyang (Frontiers in Plant Science, 2025)
IntroductionThe increasing intensity and frequency of droughts seriously threaten the structure and function of terrestrial ecosystems. In order to ensure the normal play of ecosystem service function under future stress, the temporal and spatial characteristics of ecosystem productivity response to drought need to be explored.MethodsThe net primary production (NPP) of vegetation in the Yinshanbeilu was calculated using the Carnegie-Ames-Stanford Approach (CASA) model, and subsequent study concentrated on the NPP’s geographical and temporal variable characteristics. By the calculation of the standard precipitation evapotranspiration index (SPEI), the study also sought to examine the relationship between drought and NPP at various time scales. Researchers also built drought loss rate curves based on various fertility stages using the vulnerability curve construction method.Results and discussionFindings revealed that the SPEI had varying degrees of efficacy in capturing drought conditions at various time frames. Nonetheless, the SPEI’s spatial distribution, which shows a wet distribution in the east and an arid distribution in the west, exhibited identical characteristics for all scales and may be used to indicate drought. Significant interannual variation was seen in the NPP of the study area’s vegetation, which fluctuated in an upward direction from 2000 to 2020. 75.89%, 77.23%, 81.35%, and 83.56% of the area were found to have a positive correlation between the SPEI and vegetation NPP at various time scales, with 42.53%, 48.15%, 90.72%, and 92.75% of the area passing the significance test (p < 0.05), in that order. Their results showed that as the SPEI time scale was increased, the link between vegetation NPP and SPEI became stronger. The loss rate of vegetation NPP fluctuated and grew regularly with the expansion of drought degree, varying between 20-50%, according to drought loss rate curves created for each fertility period.